Vestindo a camisa?: Dimensões do comprometimento organizacional em jovens trabalhadores - Michelle de Souza Rocha (2016)
In the new labor market's configurations, the concept of commitment has become a important predictive to understand the individual's behavior with the organization. Meyer and Allen (1991) define commitment as a three-dimensional construct, they are: affective, normative and calculative or instrumental dimensions. People with strong affective commitment remain in the organization because they want to, those with the instrumental dimension remain because they need and normative dimension stay because they feel the work as a moralobligation. Considering the commitment's dimensions described by Meyer and Allen (1991), the problem discussed in this study was how it is configured the young workers' organizational commitment. The research had explanatory and descriptive intentions and it was used mixed or "triangulation" approach. Each phase of this research was guided by astrategy of collecting and analyzing quantitative and qualitative data. The method choice is because the advantage to obtain a full view of the phenomenon. In the quantitative stage, validated questionnaires were applied about the Organizational Commitment Three- Dimensional Model of Meyer and Allen (1991), whose data were analyzed using univariateand bivariate statistics. In the qualitative phase, we proceeded content analysis process in data that it came from the interviews. Finally, the information was crossed for better understanding of young worker's organizational commitment. This young people, aged 18 and 24, areallocated into different companies' segments and attend courses run by an association aimed at their integration into the labor market. The results shows the prevalence of affective commitment, demonstrating the young workers' emotional attachment nature with the organization. The appreciation of work experience, a taste for business, the activity and thepeople were identified as major factors that support the three dimensions of commitment in young people.